Comparison of the technical condition classes of two different collections of vitrified clay sewer pipes - Kuliczkowska, Emilia; Wijas, Katarzyna (Instal, 2022)
The paper presents the results of the analysis of CCTV studies of two collections of long-operated vitrified clay sanitary sewer pipes in various cities in Poland. The aim of the analysis was to check whether there were differences in the distribution of the assignment of technical condition classes to sewer pipes in the analyzed sets. Conclusions were formulated whether the collections differed in terms of the planned renewal dates in terms of the hydraulic and operational criterion, environmental hazards and construction safety.
Keywords: vitrified clay sewer pipes; technical condition; planning of remedial actions; regression analysis; Bayesian Information Criterion